The Influence of Price, Service Quality, and Promotion on the Decision to Use GrabBike Services in Malang City: (A Study on Students of the Faculty of Administrative Sciences at Islamic University of Malang Who Use Grab Online Transportation) - Nala, Dadilla Daffa Octa; Hardati, Ratna Nikin; Trianti, Khoiriyah (Journal of International Accounting, Taxation and Information Systems, 2024)
This research aims to investigate the influence of price, service quality, and promotion on purchasing decisions using quantitative research methods. Documents and questionnaires serve as data collection tools. The research population consists of seventy FIA UNISMA students from the class of 2020 who have used the GrabBike online transportation service at least once or twice. A census approach, combining non-probabilistic and intrusive selection strategies, was employed to select a sample of seventy respondents. Data analysis was conducted using SPSS 23, involving validity and reliability testing, multiple linear regression analysis, and classical hypothesis testing. The findings indicate that: (1) Price positively influences purchasing decisions (t-value 2.928 > t-table 1.668, p ≤ 0.05). (2) Service quality significantly impacts variable Y, with a t-value of 4.078 > t-table 1.668, p ≤ 0.05. (3) Promotion also has a significant positive effect on purchasing decisions (estimated t-value 1.994 > t-table 1.668, p ≤ 0.05). Price, service quality, and promotion collectively influence purchasing decisions, supported by F-value (34.694 > F-table 2.74)